FLUKTUASI HARGA KELAPA TERHADAP PENDAPATAN MASYARAKAT KABUPATEN INDRAGIRI HILIR - nuryanti nuryanti; alexsander yandra (Jurnal Ilmiah Ekonomi Dan Bisnis, 2017)
Abstract: Fluctuations in coconut prices in Indragiri Hilir Regency affect the income level of coconut farmers. Realization is seen from the price of coconuts in 2010-2012, coconut prices rose significantly, then in 2012- 2013 coconut prices fell significantly. This has an impact on the income of unstable coconut farmers resulting in lower income of Indragiri downstream communities. One of the obstacles in increasing farmers' income is the weak bargaining position of the farmer compared to the trader. This is because the market system at the farm level is monopsoni. Factors influence the fluctuation of coconut prices ie; Company pricing , falling market demand for coconut, declining quality and quantity of coconut products. The action is to manage coconut, decrease household expenditure, the government provides guidance to handle the coconut oil into virgin coconut oil (VCO) and charcoal bracket, and rejuvenation of coconut. The next effort of the society is the formation of farmer cooperatives and advises the government to set up a coconut factory in the downstream Indragiri Regency. the monopsoni not appropriate with concept of Islamic economics. Because that one of the terms and pillar of sale and buy there must be pleasure between the seller and the buyer. Described in Surah Al-Baqarah verse 275 "Allah justifies the sale and buy and forbid usury" and surah An-Nisa verse 29-30 "Do not eat one another's treasures in the way of vanity, except by way of commerce that applies equally like among you".Keywords: Price fluctuations, Revenue